Postmortem Genetic Testing Is an Increasingly Utilized Tool in Death Investigation. Issue 4 (December 2022) - Latimer, Rebecca; MacLeod, Heather; Dellefave-Castillo, Lisa; Macaya, Daniela; Hart, Tara R.
Introduction: Postmortem genetic testing (PMGT) can provide valuable information about an individual's cause of death and potentially allow at-risk relatives to discern their risks for inherited cardiac disease. Postmortem genetic testing is most often successful with certain specimens. Methods: Investigators collected data on postmortem referrals to GeneDx, LLC for PMGT. Orders were reviewed and stratified based on provider, specimen type, and tests ordered. Discussion: This cohort included 601 deceased individuals referred for PMGT with a total of 673 genetic tests ordered from 247 different providers. The most common test categories ordered were arrhythmia (33.4%) and cardiomyopathy (29.3%). A likely pathogenic or pathogenic genetic variant was identified in approximately 15% of patients. Blood in EDTA was received for 21.6% of patients with a 95% success rate for completion of all test components. Blood samples in EDTA were most successful in completing PMGT, but sequencing was still successful in the majority of suboptimal specimens. Conclusion: The use of PMGT is increasing. Obtaining optimal samples (blood in EDTA) is important for successful completion of genetic testing. Obstacles may still exist for obtaining and storing ideal specimens. Continued efforts are needed for education and awareness around appropriate specimen types, storage and shipping of specimens, DNA banking, and overall availability of PMGT. In addition, access to resources such as supplies, proper storage conditions, DNA banking, and PMGT will allow for more opportunities to complete testing.